Slant Perception for Stairs and Screens: Effects of Sex and Fatigue in a Laboratory Environment. (April 2013) - Taylor-Covill, Guy A H; Eves, Frank F
The apparent slope of a hill or staircase, termed geographical slant perception, is exaggerated in explicit awareness. Across two experiments this paper tests the use of a laboratory environment to study geographical slant perception. First, using a student-aged sample ( N = 166), we examine the similarity of slant estimates in the field with those made in the laboratory using life-sized images of the built environment as stimuli. Results reveal no differences in slant estimates between the two test environments. Furthermore, three traditional measures of perceived geographical slant (verbal, visual, and haptic) appear sensitive to a difference in slant of only 3.4° in both the field and laboratory environments. In a follow-up experiment we test the effect of fatigue on slant estimates in the laboratory. In line with previous research with outdoor stimuli, fatigued participants provided more exaggerated explicit reports of slant relative to those in a control group, and females gave more exaggerated slant estimates than males across both experiments. The current set of findings open the door to future studies of geographical slant perception that may be more suited to laboratory conditions.